2015
DOI: 10.1051/matecconf/20153504002
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawn article – Effect of Ultrasonic-Assisted Extraction on Phenolic Content of Freshwater Macroalgae in Northern Thailand

Abstract: Effect of ultrasonic extraction on total phenolic content (TPC) of two algae; Spirogyra sp. and Cladophora glomerata was evaluated. In this study, the solid/solvent ratio of 1/30 (wt/vol) and extraction temperature of 40°C gave higher TPC value in two algae. This ratio and temperature was applied in the ultrasonic-assisted extraction (UAE) of phenolic extraction. This study compared the TPC obtained from two algae extracts without involving ultrasonic and the TPC obtained from the UAE. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to Iftikhar et al [47], the bioactive compounds that are responsible for restraining oxidation processes also lead to cardiovascular health. Cladophora produces a wide range of secondary metabolites with significant antioxidant potential, such as tocopherol [48], carotenoids [49], polyphenols [50]. Additional studies have shown the antioxidant potential of Cladophora species.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…According to Iftikhar et al [47], the bioactive compounds that are responsible for restraining oxidation processes also lead to cardiovascular health. Cladophora produces a wide range of secondary metabolites with significant antioxidant potential, such as tocopherol [48], carotenoids [49], polyphenols [50]. Additional studies have shown the antioxidant potential of Cladophora species.…”
Section: Biomedical Applicationsmentioning
confidence: 99%